Bibliometrically mapping the research field of entrepreneurial communication: where we stand and where we need to go - Manuel Kaiser; Andreas Kuckertz (Management Review Quarterly, 2023)
Entrepreneurial communication is vital for acquiring resources and building stakeholder relations in startups. This research stream has grown rapidly in recent years and has developed as a multidisciplinary field at the interface of communication and entrepreneurship. However, this rapid development and the plethora of associated perspectives have led to a diverse and fragmented research field with different foci and concepts, making structural overviews difficult. Against this background, we conducted a bibliometric analysis to uncover the hidden structure of previous entrepreneurial communication research and to guide scholars toward a future research agenda. First, we identified 383 articles via the Scopus database, published in 245 academic sources, that covered nearly 50~years of research. We then connected the results of previous research using co-occurrence analysis and a thematic map to highlight the intellectual structure of the field and offer insights into its research clusters. Our algorithmic historiographic analysis illustrates the development of the field over time and highlights upcoming topics. Overall, entrepreneurial communication is crucial, particularly for startups engaging in resource acquisition for employee and investor relations with venture capitalists and business angels.
Keywords: L26; M13; 650; Bibliometric analysis; Entrepreneurial communication; Historiography; Startup; Thematic map